Tumor Induced Osteomalacia - Kinnaree, Chaloempol; Panya-amornwat, Thanita; Methathien, Athikom; Laungwitchajareon, Yongyot (Journal of Southeast Asian Orthopaedics, 2022)
Objective: Tumor induced Osteomalacia (TIO) is a rare paraneoplastic syndrome which mostly caused by mesenchymal cell tumors that secrete a phosphaturic hormone called fibroblast growth factor-23 (FGF-23). These FGF-23-secreting tumors have its uniqueness of being a small tumor which are deep-seated inside patient’s body and they are very difficult to be located. This report is about an epidural mesenchymal tumor adjacent to 6th thoracic vertebrae. Method: To locate the culprit tumor using thorough physical examination, clinical radiographs with functional imaging and laboratory investigations in a 71-year-old female patient presented to our office with TIO. Result: A 71-year-old female came with chief complaints of moderate body pains, muscle weakness and increasing thoracic kyphosis in 2 years. Laboratory investigation shows hypophosphatemia. Plain radiographs found pseudofracture of distal phalanx of her right thumb without any history of trauma. Parathyroid scan (MIBI + Pertechetate) shows an enhancing nodule measuring about 0.5×1.1 cm locate at lower pole of right parathyroid gland with further imaging of MRI Neck and Thorax found an epidural elongated mass measuring about 0.8×1.3×2 cm adjacent to 6th thoracic vertebrae. By the 6th day after tumor removal, serum phosphorus level reached normal range. Patient’s symptoms were improved without phosphorus supplements. Histological reports show its cell type as spindle cell tumor. Conclusion: TIO is body conditions response from over-regulated FGF-23 secretion of small soft tissue tumor. which very difficult to be located. Once complete tumor resection is done, TIO will be complete cured.